Born into adversity; The intergenerational transmission of psychological morbidity in second generation Irish children living in Britain. (13th September 2011) - Das-Munshi, J; Clark, C; Dewey, ME; Leavey, G; Stansfeld, S; Prince, MJ
Abstract : Objective: Despite relative improvements in socioeconomic position across generations, Irish people living in Britain continue to suffer from excess psychological morbidity. This study will aim to elucidate factors relating to the intergenerational transmission of psychological morbidity. Method: Data from two birth cohorts; the 1958 National Child Development Survey (NCDS) and the 1970 British Birth Cohort (BCS70) were used. Both surveyed 17, 000 babies born in a single week in 1958 and 1970. 5% of each cohort comprised second-generation Irish children. Data from ages 7, 11, and 16 in the NCDS, and ages 5, 10 and 16 in BCS70, were used to assess childhood adversity and psychological morbidity, as well as mental and physical health of Irish-born parents. Results: In both cohorts, second generation Irish children were more likely to be born into and brought up under circumstances of marked material hardship. Relative to children without a parental history of migration, second generation Irish children born in 1958 had greater emotional and behavioural problems at ages 7, 11 and 16, while Irish children born in 1970 had greater emotional and behavioural problems at age 16. All mental health differences were fully accounted for through material adversity indicators. In NCDS, Irish-born parents were more likely to report a chronic health problem relative to non-Irish parents (OR: 1.29; 95% CI: 1.08 to 1.54; p=0.005). In BCS70 Irish-born mothers were 1.39 times more likely to have a common mental disorder when their children were aged five (95% CI: 1.15 to 1.69; p<0.001). The excess risk of mental or chronic health problems in Irish-born parents disappeared when material adversity was taken into account. Maternal common mental disorders fully mediated psychological morbidity in second generation Irish children, whereas parental chronic health problems partially mediated differences. Conclusion: Childhood mental health problems in second generation Irish children growing up in Britain are accounted for through the adverse social circumstances which they were born into. As childhood mental health is implicated in the aetiology of adult common mental disorders, the findings suggest important life-course mechanisms in the aetiology of adult mental health in second generation Irish people.